Differential development of acute tolerance may explain heightened rates of impaired driving after consumption of alcohol mixed with energy drinks versus alcohol alone. - Marczinski, Cecile A.; Stamates, Amy L.; Maloney, Sarah F. (Experimental & Clinical Psychopharmacology, 2018)
Consumers of alcohol mixed with energy drinks (AmED) are more likely to drive while impaired when compared to alcohol alone consumers. In addition, acute tolerance to the internal cues of feelings of intoxication is known to contribute to maladaptive decisions to drive while impaired. Therefore, the purpose of this study was to determine whether there is differential development of acute tolerance for AmED versus alcohol alone for ratings of willingness to drive after alcohol consumption. Social drinkers (n = 12) attended 4 separate sessions where they received alcohol and energy drinks, alone and in combination. The development of acute tolerance to alcohol was assessed for several objective (a computerized cued go/no-go reaction time task) and subjective measures at matched breath alcohol concentrations (BrACs) for the ascending and descending limbs of the BrAC curve. The results indicated that alcohol administration decreased willingness to drive ratings. Acute tolerance was observed in the AmED dose condition for only the willingness to drive ratings that were significantly higher on the descending versus ascending test. Alcohol-induced impairments of the computer task performance did not exhibit any acute tolerance. Therefore, the differential development of acute tolerance may explain why many studies observe higher rates of impaired driving for AmED consumers compared to alcohol alone consumers. Because drunk driving is a major public health concern, alcohol consumers should be warned that the use of energy drink mixers with alcohol could lead to a false sense of security in one's ability to drive after drinking. (PsycINFO Database Record